2012
DOI: 10.1063/1.3698281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sputtered lanthanum hexaboride film thickness on field emission from metallic knife edge cathodes

Abstract: Breakdown voltage reliability improvement in gas-discharge tube surge protectors employing graphite field emitters J. Appl. Phys. 111, 083301 (2012) Space charge and quantum effects on electron emission J. Appl. Phys. 111, 054917 (2012) Enhanced electron field emission from plasma-nitrogenated carbon nanotips J. Appl. Phys. 111, 044317 (2012) Field-emission properties of individual GaN nanowires grown by chemical vapor deposition J. Appl. Phys. 111, 044308 (2012) High emission currents and low threshold fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For applications that subject mixed-metal hexaboride compounds to high currents, , it is important to understand the behavior of these solid solutions from the perspective of diffusion and mass transport mechanisms. In general, increased reactivity in the presence of current in metallic and intermetallic diffusion couples has been attributed to enhanced mobility of defects, , enhanced product growth rate, and enhanced nucleation of product phases. , Examples of the effect of current on mass transport include the increased dissolution of Ni in liquid Al, increased neck growth between copper spheres and plates, and increased product phase formation between Sn/Ni, Sn/Ag, Bi/Ni, Al/Ni, Al/Au, Ag/Zn, and Si/Mo diffusion couples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For applications that subject mixed-metal hexaboride compounds to high currents, , it is important to understand the behavior of these solid solutions from the perspective of diffusion and mass transport mechanisms. In general, increased reactivity in the presence of current in metallic and intermetallic diffusion couples has been attributed to enhanced mobility of defects, , enhanced product growth rate, and enhanced nucleation of product phases. , Examples of the effect of current on mass transport include the increased dissolution of Ni in liquid Al, increased neck growth between copper spheres and plates, and increased product phase formation between Sn/Ni, Sn/Ag, Bi/Ni, Al/Ni, Al/Au, Ag/Zn, and Si/Mo diffusion couples.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion is enhanced toward the positive electrode, and profiles match well with error functions displaying classic Boltzmann–Matano , concentration-dependent diffusivity. This effect of electric field on cation diffusion is an important consideration for applications such as field emitters , utilizing mixed-metal MB 6 compounds, as diffusion may lead to inhomogeneity of the solid solution . In addition, we propose that the mobility of the metal ion within the rigid boron sublattice presents an opportunity to use these materials as hosts for the storage of atoms or ions, if transport can be reversibly controlled using, for example, electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the challenge of realizing high-crystallinity or epitaxial thin films with optimum surface orientation to achieve low work function for electron emission in spite of its complexity in crystal structure and the bonding. Various techniques such as sputtering, [12][13][14] pulsed laser deposition, 15,16) and electron beam deposition (EBD) [17][18][19] have been used for thin film preparations. For EBD, epitaxial LaB 6 films have been demonstrated on MgO 17) and on MgO/ sapphire with a SrB 6 buffer layer.…”
mentioning
confidence: 99%
“…This very low FF is due to the presence of an S-shaped feature on the I – V curve (Figure ). The S-shape phenomenon in organic solar cells has been extensively studied, and it is generally due to the presence of a potential barrier or poorly conductive layer at an interface in the device. The resistivity of LaB 6 layer can vary greatly depending on the deposition method and the film thickness, , and Winsztal et al showed that the resistivity increases dramatically when the LaB 6 film’s thickness is less than 50 nm (10 6 Ω·cm for 25 nm thick polycrystalline LaB 6 ) . A very low value for the conductivity of the deposited LaB 6 layer could be the reason for the appearance of an S-shape feature in the devices with 5 nm thick LaB 6 layer.…”
Section: Resultsmentioning
confidence: 99%